2015
DOI: 10.1071/ch15191
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Restructuring of Copper Surfaces Using Organic Additives and Its Effect on the Electrocatalytic Reduction of Nitrate Ions

Abstract: This work describes the fabrication of nanostructured copper electrodes using a simple potential cycling protocol that involves oxidation and reduction of the surface in an alkaline solution. It was found that the inclusion of additives, such as benzyl alcohol and phenylacetic acid, has a profound effect on the surface oxidation process and the subsequent reduction of these oxides. This results in not only a morphology change, but also affects the electrocatalytic performance of the electrode for the reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…For the Cu electrode there are additional processes in the anodic sweep from 0.70 to 1.00 V which are attributed to the oxidation of Cu to Cu 2 O and the oxidation of both Cu and Cu 2 O to a mixture of Cu(OH) 2 and CuO. 50 It is likely that such extensive oxidation of the surface with oxides of Cu inhibit the activity of the surface for the OER as it is known that only appreciable current densities can be achieved at copper oxides at overpotentials of ca. 0.60 V or greater.…”
Section: Resultsmentioning
confidence: 99%
“…For the Cu electrode there are additional processes in the anodic sweep from 0.70 to 1.00 V which are attributed to the oxidation of Cu to Cu 2 O and the oxidation of both Cu and Cu 2 O to a mixture of Cu(OH) 2 and CuO. 50 It is likely that such extensive oxidation of the surface with oxides of Cu inhibit the activity of the surface for the OER as it is known that only appreciable current densities can be achieved at copper oxides at overpotentials of ca. 0.60 V or greater.…”
Section: Resultsmentioning
confidence: 99%
“…The overall magnitude of the response increases with cycling (as indicated by the arrows showing the increasing current response), which indicates an increase in the surface area of the electrode. It should be noted that this increase is less than that observed when the Cu foil is restructured in 1 M NaOH only ( Figure S1 ), as seen in our previous work [ 13 ], due to the presence of ethanol in the electrolyte and is discussed below. On the anodic sweep peak A 1 is due to the Cu/Cu 2 O transition followed by process A 2 , which is split into two components namely oxidation of unoxidized Cu 0 and Cu 2 O to CuO and Cu(OH) 2 .…”
Section: Resultsmentioning
confidence: 48%
“…This phenomenon has been taken advantage of for other metals, which have been restructured by applying oxidation/reduction protocols that initially form an oxide on the surface followed by reduction. The frequency and duration of the oxidation/reduction processes influences the morphology, number of active sites and hence electrocatalytic activity and has been demonstrated for Au and Cu surfaces [ 11 , 12 , 13 ]. Our recent work on the electrochemical restructuring of copper indicated that the presence of additives in the electrolyte can significantly influence the morphology of the surface and the extent of residual oxides, which impacted on electrocatalytic performance [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The electrodeposition of nanostructured materials is an area of intense research due to the ability to form highly active surfaces which are not inhibited by surface capping agents. [1][2][3][4][5][6][7][8][9][10] The process of electrodeposition or electrochemical restructuring [6,[10][11][12] of surfaces allows metastable states to be attained and high energy facets to be exposed to solution which aids in both catalytic and electrocatalytic processes. Other advantages include experimental simplicity, control over shape, size and composition and good adherence to underlying supports.…”
Section: Introductionmentioning
confidence: 99%